EVALUASI DAMPAK TRANSPORTASI PADA PERTUMBUHAN EKONOMI DAN EVALUASI KINERJA INFRASTRUKTUR JALAN, STUDI KASUSU JALAN JAMIN GINTING MULAI DARI PASAR PANCUR BATU S/D PASAR LAU CIH - Sheila Hani; Nirmadarningsih Hiya (Universitas Methodist Indonesia, 2023)
Medan, as the capital of North Sumatra, is experiencing rapid growth which increases demand for transportation infrastructure. This condition causes various problems, such as difficulties in spatial planning and transportation problems on main roads. Therefore, research was conducted to evaluate the volume, characteristics and performance of traffic on Jalan Jamin Ginting Km.12, Lau Cih Village to Jalan Jamin Ginting Km. 21 Namoriam Pancur Batu Village. Data collection methods involve direct surveys, including traffic volume, speed, and road capacity. From the survey results, it is clear that during the morning peak hours the traffic volume from the direction of Pancur - Lau Cih is greater than the opposite, in contrast to the non-peak hours of the afternoon and evening peak hours, it is known that the traffic volume from the direction of Pancur - Lau Cih is greater than that from Lau Tch - Pancur and the condition of the 4/2 D road with a capacity value of 5,474 pcu/hour can still accommodate traffic flow in the next 10 years. For peak hours (morning and afternoon) because the DS value is very close to service level category A, namely 0.07 at morning peak hours, and 0.14 at afternoon peak hours so that the road service level is included in category A (DS<0.54) for morning and evening peak hours, category A (DS<0.35) for afternoon non-peak hours. Jalan Jamin Ginting is still able to serve vehicle volumes as evidenced by the results of calculating the degree of saturation, namely 0.633 < 0.75, which is a requirement for the maximum road performance limit. Even though the road is still able to accommodate the volume of vehicles, other problems such as the Pancur Batu market also affect the road's performance.